KOMPOSISI COLEOPTERA PERMUKAAN TANAH DI TIGA LOKASI DESA PENARIK KECAMATAN PENARIK KABUPATEN MUKOMUKO - -, Oktavianra - (STKIP PGRI Sumbar, 2014)
District of village forest area Penarik Mukomuko district has become an area of oil palm plantations (monoculture), it is expected to affect the condition of the ground vegetation and animals. One of the damage is the loss of biodiversity and habitats for some types of Coleoptera. This study aims to determine the composition of the soil surface Coleoptera chemical and physical factors.The study was conducted in February and March 2014 sampling was done in the Garden District of Palm Penarik Mukomuko district. The study used a descriptive survey method by means of direct collection using pitfall traps. Identification of surface soil samples Coleoptera conducted at the Laboratory of Zoology Biology Education Program STKIP PGRI West Sumatra, vegetation identification is done at ANDA Herba Laboratory, State University of Andalas Padang. Measurement of soil organic C content in Soil Chemistry Laboratory of the Faculty of Agriculture, University of Andalas Padang.Soil surface Coleoptera found that as many as 4 family consists of 10 genera and 20 individuals. At the station I found two families, consisting of 4 genera and 6 individuals, at station II was found four families, consisting of 8 genera and 8 individuals, and the station III found one family, consisting of 4 genera and 6 individuals. At the station I the highest relative density is Anoplognathus (32.50%), the lowest relative density is the Onthophagus and Casida, (17.50%). At the station II relative density equal to the genus of Coleoptera Casida, Dermentes, Lytta, Euphoria, Lepidiota, Onthophagus, Oryctes, and Xyloryctes ie (12.50%). Relative density is highest at the station III Anoplognathus genus (32.50%) and the lowest relative density is the genus Onthophagus Nicaqus and 17.50%.